The interdependence of foreign exchange vulnerability in emerging markets. Issue 2 (7th April 2022) - Qureshi, Saba; Aftab, Muhammad; Hegerty, Scott
Abstract : Purpose: The foreign exchange market plays a crucial role in defining the overall health of an economy. In these times of globalization and (in some ways) deglobalization, these markets are highly vulnerable to external shocks. In this line of research, this study investigates exchange-market vulnerability among the BRICS economies by considering the co-movements among variables and contagion among markets. Design/methodology/approach: This study uses DCC-IGARCH and Wavelet approaches to examine interdependence and contagion among the foreign exchange markets of the BRICS countries. The prior approach gives exposure to correlations over time, while the latter approach is suitable to provide insight regarding correlations over different frequency and time domains. Findings: These results show evidence of meaningful co-movements in the vulnerability of the BRICS economies' foreign exchange markets during periods of market instability. The authors observe that interdependence significantly increased after 2008 and is prominent in the short run, particularly up to the scale of 1.5 years. In addition, there is evidence of persistent integration across the short and medium run. Furthermore, the findings indicate recurrent patterns of co-movements and the presence of contagion. Originality/value: Given the high degree of economic integration among the BRICS economies, there is relatively little literature on how each member country's foreign exchange vulnerability can affect others. This research fills this gap, by applying appropriate econometric techniques and using a newly created measure of exchange market vulnerability that is unit consistent—such that it combines observed change in exchange rates with the change that is prevented through central bank intervention in a common unit, rather than by combining percentages with dollar-denominated values. This research provides important implications for investors and policymakers.